Influence of adding earl flower extract (Clitoria Ternatea L.) on the fruit leather quality of kersen fruit (Muntingia Calabura L.) - Lusi Hardianingsih; Adi Saputrayadi; Syirril Ihromi (Journal of Agritechnology and Food Processing, 2024)
Fruit leather is a thin sheet-shaped processed product with a distinctive consistency and flavor according to the type of fruit used as its main raw material. This study aims to determine the effect of the addition of telang flower extract on the quality of fruit leather of kersen fruit and to determine the right addition of telang flower extract in making fruit leather of kersen fruit. This study used a Completely Randomized Design (CRD) which analyzed the results with the Honest Real Difference Test (BNJ) at the 5% level with one factor treatment, namely the addition of telang flower extract consisting of 5 treatments: P0 (0%: 200 gr of kersen fruit pulp as control), P1 (25%: 200 gr), P2 (30%: 200 gr), P3 (35%: 200 gr) P4 (40%: 200 gr). Based on the results of data analysis, it is known that the treatment of adding telang flower extract has a significant effect on chemical properties (water content, antioxidant activity and vitamin C) as well as organoleptic properties of color and texture, but has no significant effect on organoleptic aroma and taste). Where, the higher the addition of telang flower extract, the moisture content, antioxidant activity and vitamin C content of fruit leather will increase. The best treatment based on the organoleptic test results is treatment P4 (addition of 40% telang flower extract) with very purple color criteria, preferred aroma and taste, very chewy texture, 19.69% moisture content, IC50 94.84 ppm, and with vitamin C content of 1856.13 mg/100g.